Respon Pertumbuhan Stek Pucuk Kenanga (Cananga odorata) terhadap Pemberian Media Tanam dan Zat Pengatur Tumbuh - Irdika Mansur; Taufan Nugraha (Jurnal Silvikultur Tropika, 2022)
Essential oil which is contained on most trees is one of the promising Non-Timber Forest Products (NTFPs) that need to be explored and developed further, for the oil is relatively safe and stores major benefits for local people. There are around 9 -12 types of essential oil that is being developed and one of them is cananga oil, which is available through distillation process of the flowers. The research aims to investigate the ability of cananga to be propagated trough shoot cuttings method, to discover the effects of growing media and plant growth regulators toward the shoot cuttings’ growth and to determine the suitable growth media and plant growth regulators for the cuttings’ development. The collected data were survival rate in percentage, root growth in percentage, height growth, numbers of developed leaf, numbers of developed primary and secondary roots, and also the length of primary roots. The addition of plant growth regulators gave a significant effect toward survival rate (in percentage), height growth and the numbers of developed leaf of the species whereas the addition of growing media and the interaction between the treatments did not give significant effect on the observed traits. All type of media options could be used for cananga shoot cuttings method and the best growth regulator identified in live percentage parameters, high growth and number of leaves on cananga shoot cutting is Rotoone-F. However, in case of rooting, the best growth regulator is found in addition of Rapid root. Keywords: Cuttings, Cananga, Media, Plant Gowth Regulator